Effects of Different Dietary Levels of Blue Lupine (Lupinus angustifolius) Seed Meal With or Without Probiotics on the Performance, Carcass Criteria, Immune Organs, and Gut Morphology of Broiler Chickens - Al-Sagan, Ahmed A.; AL-Yemni, Abdullah H.; Al-Abdullatif, Abdulaziz A.; Attia, Youssef A.; Hussein, Elsayed O. S (Frontiers in Veterinary Science, 2020)
The aim of this study was to investigate the effects of different dietary levels of blue lupine (Lupinus angustifolius) seed meal with or without probiotics (Bacillus subtilis) in broiler diets on the growth performance, carcass characteristics, internal and immune organs, and gut morphology. Three experimental diets containing 0, 20, and 30% of blue lupine, with or without probiotics, were formulated and fed to 144-day (d)-old Ross 308 broiler chickens. Overall, chicks fed blue lupine meal diets, especially at the 30% rate, showed improved growth, feed performance parameters, and carcass characteristics in comparison to chicks fed a soybean meal-based diet. For example, a 30% blue lupine diet resulted in a significant increase in the duodenum length percentage of 35-d-old broilers; the addition of probiotics had no - effects on the dressing, thigh, and leg percentages of 21- and 35-d-old broilers and the drumstick and leg percentages of 35-d-old broilers. In conclusion, a 30% blue lupine seed diet with the addition of probiotics could provide a cheap source of protein without negative effects on the growth performance, carcass characteristics, immune organs and gut morphology of broilers.